Ethical considerations for equitable outcome-based education in the Metaverse: a qualitative study - Mohamed Sofiadin, Aidrina (Universiti Teknologi MARA (UiTM) Cawangan Pahang, 2025)
The integration of Outcome-based education (OBE) into Metaverse environments promises new opportunities for immersive, authentic, and competency-driven learning experiences. However, it also presents profound ethical challenges, particularly concerning equity, accessibility, privacy, and fairness. This qualitative study investigates two research questions: (1) What ethical concerns do learners and educators identify about implementing OBE in Metaverse environments? (2) What design, policy, and pedagogical practices are recommended to mitigate inequities and value learners’ rights and dignity? Semi-structured interviews were conducted with 11 XR experts across education, design, and policy domains. Thematic analysis revealed three primary ethical concerns: digital access inequities, bias in assessment algorithms, and privacy and data governance risk. Recommendations emerging from the study include equity-first design principles, theoretical assessment frameworks, robust data governance policies, and culturally responsive pedagogical approaches. The findings provide an evidence-based framework to guide ethical deployment of OBE in Metaverse learning environments.